Developing Metacognitive Model on In-Service Teacher’s Academic Writing Through Virtual Flipped Classroom - Enny Dwi Lestariningsih; Testiana Deni Wijayatiningsih (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
The current study has two objectives. The first is to describe the process of developing a metacognitive model on in-service teachers’ academic writing through virtual flipped classrooms and then secondly, to investigate the teachers’ research writing interests using a metacognitive model on in-service teachers’ academic writing through virtual flipped classrooms. This research was conducted in the Demak regency. The researchers also used the Research and Development method. Validation results exemplify that the application of a metacognitive model to academic writing in the in-service teachers through virtual flipped classroom specifically used appropriate teaching materials to be used in classroom teaching, the attention is given to the outcomes of the validation, such as; the concept of conformance indicators, material performance indicators, demonstration indicators, and capability indicators. This proves that the metacognitive model on in-service teachers’ academic writing through virtual flipped classroom applications runs smoothly and according to what is expected. In addition, it has positive interests from the teachers which could give good impact in their writing research article.